Tarian Rakyat Sumbawa: Upaya Pelestarian dan Perkembangannya = Sumbawa Folk Dances, Its Perpetuation And Development - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The problem formulated in this research is focused on the existence of many indicators of alteration and adoption of aesthetics vision into showing art production of traditional dance in Sumbawa cultural group. However, there is no real effort to perpetuate the tradition of folk dances, and also no special attention given to develop its tradition in accordance with special features and genuine motives which is an identity of a region. This is important because western influences are beginning to emerge in these cultural aesthetics. Unfortunately, those who are involved in these process still do not realize such alien influences. This research method was based on observation, interview, and collection of dance inventory material from special dance books, articles and papers about dances. A variety of research outcomes and a general conclusion could be drawn from these folk dances of Sumbawa territory. It was found that these dances are still prote